Estudio de mercado para la construcción de un resort que fomente el desarrollo turístico rural en el cantón Chone - Chávez Roca, Rosa Elvira (2017)
The present research has as general goals to develop a market study for the construction of a resort that foments the rural tourism development of the canton Chone; The methodology used was based on the analysis of the criteria about four authors, Vela (2012), Espinoza (2013), Fassler (2013), Salazar and Yánez (2014); Carrying out as a first phase a situational diagnosis of the generalities, antecedents, attractions and characteristics of the tourist accommodation, in turn gathering information of the different activities that are developed in that region, from the agricultural activity and its main products; The livestock activity, and the trade that is located in the third economic area of the Manabí territory. The second phase consists of the analysis of the supply, demand and competition in which the preferences of the tourist were determined, the different tourist accommodations of the canton and of the regions close to it were evaluated, in turn the tastes and requirements of The visitors, obtaining as a result that the demand is directed to national clients; As a third and final phase, the product marketing mix was designed in which promotion and publicity strategies were proposed, the positioning of the logo and the slogan, as well as the price and different distribution and promotion channels to support the present work. Based on the results obtained in the survey it was found that there is an acceptance of 83% of tourists who believe that it is feasible to create a Resort in the Chone canton.